Análisis y proyección del consumo de energía eléctrica ante confinamiento por emergencia sanitaria en el área de concesión de la empresa eléctrica provincial Cotopaxi. Caso de estudio cantón Latacunga. - Estrella Tapia, Diego Fernando (2021)
This document analyzed the impact that occurred as a result of the arrival of the pandemic in the region, which forced the taking of a sequence of health protection measures that produced a drastic decrease in economic activity from the decree of mandatory confinement of people in their homes. households in most countries. Thus, the electricity supply distribution companies encountered a major problem, as they were unable to register the meter readings in person, for the respective monthly billing, which has led to the use of an erroneous method for the calculation and estimation of average energy consumption that was later assigned to each of the users, since no previous behavior can be equal to that of the quarantine of the year 2020. For this, the significant ups and downs of energy consumption in the different types of subscribers were analyzed. in concession of ELEPCO SA belonging to the Latacunga canton, through a statistical projection model of electricity consumption that establishes probabilistic values that simulate typical consumption in times of human confinement, which are validated with the record of measured information and data projected by the probabilistic model applied through the methods of moving averages and ordinary least squares, determining an evident decrease in energy consumption at a general level of the analyzed users, but failing that each type of user charged has its own behavior under these circumstances of confinement.